The Dark Side of Controlling Shareholders Equity Pledges for Corporate Green Innovation - Shu Hsien Lin; Wang Kuei Yuan; Leszek Niewdana; Lin Zih Ying (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
Green innovation is fundamental to sustainable development but frequently encounters financial and governance constraints in newly industrialized and export-oriented economies. Controlling shareholders' behaviors, particularly equity pledges, may erode firms' long-term innovation incentives. This study investigates how controlling shareholders' equity pledges influence corporate green innovation in Taiwan and explores the underlying mechanisms and contextual variations of this relationship. The research focuses on Taiwan Stock Exchange (TWSE) and Taipei Exchange (TPEx) listed companies over the period from 2013 to 2023, offering insights from a high-technology economy in which green transformation ambitions coexist with concentrated family ownership structures and active equity pledging practices. Using panel data regression analysis and mediation models, this study examines the direct impact of equity pledges on green innovation and further analyzes three mediating channels: Environmental, Social and Governance (ESG) performance, financing constraints, and tunneling behavior. The results show that controlling shareholders' equity pledges significantly reduce firms' green innovation efforts, primarily by lowering research and development (R&D) investment. The adverse effects operate through worsened ESG performance, tighter financing constraints, and increased tunneling activities. However, the inhibitory effect is mitigated in firms with low pledge ratios, high pollution levels, or government-linked ownership structures. Equity pledging by controlling shareholders poses a substantial threat to green innovation in most Taiwanese firms, although certain firm characteristics can buffer this effect. This article contributes to the literature by uncovering the dark side of shareholder pledging behavior in the context of environmental innovation within a high-technology export economy, highlighting the need for regulatory scrutiny and corporate governance reforms to safeguard long-term sustainable development.